1997
DOI: 10.1002/pro.5560061116
|View full text |Cite
|
Sign up to set email alerts
|

Covalent methionylation of escherichia coli methionyl‐tRNA synthethase: Identification of the labeled amino acid residues by matrix‐assisted laser desorption‐ionization mass spectrometry

Abstract: Methionyl-adenylate, the mixed carboxylic-phosphoric acid anhydride synthesized by methionyl-tRNA synthetase (MetRS) is capable of reacting with this synthetase or other proteins, by forming an isopeptide bond with the eNH2 group of lysyl residues. It is proposed that the mechanism for the in vitro methionylation of MetRS might be accounted for by the in situ covalent reaction of methionyl-adenylate with lysine side chains surrounding the active center of the enzyme, as well as by exchange of the label between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The consistency among the different assays suggests that despite the selfmethionylation by the enzyme, the kinetics of aminoacylation in the presence of tRNA is unaffected. This is consistent with the notion that the self-methionylation reaction occurs at a much slower rate relative to aminoacylation (Gillet et al 1997), so that the self-methionylation was not detected in the time scale of one turnover of aminoacylation.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The consistency among the different assays suggests that despite the selfmethionylation by the enzyme, the kinetics of aminoacylation in the presence of tRNA is unaffected. This is consistent with the notion that the self-methionylation reaction occurs at a much slower rate relative to aminoacylation (Gillet et al 1997), so that the self-methionylation was not detected in the time scale of one turnover of aminoacylation.…”
supporting
confidence: 90%
“…A set of mixing controls established that the observed reaction rates were independent of the premixing of the reactants. Additionally, because EcMetRS has an ability to self-methionylate to lysine residues near the active site (Gillet et al 1997), as evidenced in the self-labeling by covalent incorporation of 35 S-Met to the enzyme in both the presence and absence of tRNA Met (Supplemental Fig. S1A,B), aminoacylation was also monitored by two different methods.…”
Section: Kinetic Analysis Of Ecmetrsmentioning
confidence: 99%
“…The low levels of self biotinylation and promiscuous protein biotinylation by wild type BirA observed in vivo seems likely to be a consequence of over expression of the enzyme resulting in an intracellular BirA concentration that greatly exceeds the supply of apo-BCCP, the normal biotin acceptor. In vitro methionyl-tRNA synthetase self modification is suppressed by addition of the tRNA acceptor (Gillet et al 1997) and we expect the apo BCCP would have a similar effect on BirA self modification in vivo. Indeed, a wild type E. coli cell contains only about ten or so molecules of BirA and BCCP is normally present in great excess.…”
Section: Discussionmentioning
confidence: 89%
“…The observed self modification was not unexpected, since two other enzymes that synthesize acyl-adenylate intermediates, the methionyl-tRNA synthetases of E. coli and Bacillus stearothermophilus, have been shown to catalyze self methionylation (Gillet et al 1997;Hountondji et al 2000). In these enzymes it was reported that once methionine was activated by ATP to form methionine-5Ј-AMP, the reactive lysine side chains closest to the acyl-adenylate were those modified (Hountondji et al 2000).…”
Section: Discussionmentioning
confidence: 92%
“…Troubleshooting 3.4.1 Acid gel electrophoresis to confirm the location of the mischarged amino acid-Protein co-precipitates with tRNA during TCA precipitation (Section 3.3). Under conditions where the enzyme's charging activity is weak, such as during mischarging, it is possible for the enzyme to become self-labeled with radiolabeled amino acids (72)(73)(74). In addition, radiolabeled amino acid may be trapped in the protein's active site and also coprecipitated.…”
Section: Assay To Measure Deacylation Of Ala-trna Promentioning
confidence: 99%